Exposure to hand-arm vibrations in orthopaedic plaster room: risk management - Lembo, Marco; Lunghi, Alessandro; Leo, Erica; Ritrovato, Matteo; Cannatà, Vittorio; Capussotto, Carlo; Tirabasso, Angelo; Zaffina, Salvatore; Camisa, Vincenzo; Derrico, Pietro; Martella, Mauro; Marchetti, Enrico (La Medicina del Lavoro, 2016)
Background: In hospitals, the use of vibrating tools, such as oscillating saws to cut plaster, can expose the staff to hand-arm vibrations. Objectives: The aim of the study was to assess the exposure of workers to vibrations in the plaster room and then identify the most appropriate intervention for prevention and protection to be implemented in order to minimize exposure and protect workers’ health, considering different individual hyper-susceptibility conditions. Methods: Four different models of plaster saws were examined for the evaluation. Various measurements were made in normal working conditions of the operators. Results and conclusions: The values of acceleration and noise detected on the instruments were in line with those reported in the literature. The preventive measure adopted (replacing plaster saws currently used in the hospital with similar ones with lower vibration emission) was an adequate means of protection. Health surveillance activities recorded a higher level of wellbeing, both environmentally and individually and, specifically, an increased protection level for the hyper-susceptibility conditions observed during health checks of exposed personnel which will be monitored regularly by the Occupational Health Service.